2023
DOI: 10.1039/d2lc00963c
|View full text |Cite
|
Sign up to set email alerts
|

Tumour associated vasculature-on-a-chip for the evaluation of microbubble-mediated delivery of targeted liposomes

Abstract: The vascular system is the primary route for the delivery of therapeutic drugs throughout the body and is an important barrier at the region of disease interest, such as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…Integrin expression and interactions with RGD peptides may change between cell lines and subtypes. HCT116, HT‐29, SW620, Caco‐2, LoVo, LS174T, DLD‐1, SW480, and Colo205 colorectal cancer cell lines contain integrin αvβ3, which can interact with RGD peptides 234,238 . The RKO cell line has been demonstrated to interact with RGD peptides, which can attach to integrin αvβ5 239,240 …”
Section: The Rgd Peptide In Cancer Targetingmentioning
confidence: 99%
“…Integrin expression and interactions with RGD peptides may change between cell lines and subtypes. HCT116, HT‐29, SW620, Caco‐2, LoVo, LS174T, DLD‐1, SW480, and Colo205 colorectal cancer cell lines contain integrin αvβ3, which can interact with RGD peptides 234,238 . The RKO cell line has been demonstrated to interact with RGD peptides, which can attach to integrin αvβ5 239,240 …”
Section: The Rgd Peptide In Cancer Targetingmentioning
confidence: 99%
“…The treatment of exosomes carrying microRNA showed decreased cancer cell invasion (white arrows) as well as inhibition of the endothelial reorganization into tubular constructs [ 72 ]. C Liposomes were loaded in microbubbles that were collapsed using inertial cavitation induced by ultrasound in the vascular bed, enabling the deposition of the liposomes [ 112 ] …”
Section: Drug Delivery Development Based On Vascularized Tumor Modelsmentioning
confidence: 99%
“…They showed that this microRNA substantially curbed cancer migration, as well as angiogenesis by suppressing VEGF-A and VEGFR2 expression. An ingenious DDS used microbubbles to deliver loaded liposomes at the tumor site, combined with ultrasound both to permeabilize cell membranes and to make microbubbles collapse to release their content [ 112 ] (Fig. 5 C).…”
Section: Drug Delivery Development Based On Vascularized Tumor Modelsmentioning
confidence: 99%
“…As a result, αvβ3 holds promise as a therapeutic target for cancer treatment. 59 Additionally, the vascularized tumor microfluidic chip platform can be utilized to investigate the impact of stromal cells on tumor cell attachment and growth, as well as the effects of tumor cells on blood vessel and mesothelium permeability in early and late metastasis models. 60 To better replicate the interaction between cancer cells and the tumor environment and enhance the prognosis of neuroblastoma, the Michael research team has designed a microvascular neuroblastoma tumor environment chip.…”
Section: ■ Organs-on-chipsmentioning
confidence: 99%